Estudo de estrelas B do campo 13 da missão Kepler/K2 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
With the advent of the Kepler telescope, high-precision photometric data were obtained during its original mission and by the Kepler/K2 mission. In this work, one of the goals is to analyze the variability of 68 stars of spectral type B, observed during campaign 13 (C13) from K2 mission. The purpose of classification in the photometric field is to seek to fill the gap of the star charac- terizations of these campaigns, following the most appropriate and recent literature. Likewise, it is desirable to obtain the values of the atmospheric parameters of these stars. Therefore, the collection of spectral samples is necessary, which it is commited through ground observation at the Pico dos Dias Observatory (OPD), and via the database of the LAMOST telescope as a complement. Information from spectroscopy is essential to characterize the atmospheric structure of observed stars. In parallel, it contributes to the determination of evolutionary parameters, such as mass, radius, and luminosity. The complementation in the characterization of the atmospheric and evolutionary parameters are relevant in the constitution of the Hertzprung-Russel (H-R) diagram for the observed targets. Still dealing with the spectroscopic front, there is the follow-up in the profile of the Hα lines for stars that present emission. By means of the methodology of stellar seismology, the asteroseismology, the subclasses of stars that present coherent modes of pulsations driven by the κ-mechanism, can be distinguished. By investigating the frequency spectra, these pulsation modes must be distinct due to gravity (g modes) or due to pressure activity in the star (p modes). Stars that have prograde gravity modes must be analyzed in order to obtain the average rotation frequency and its respective characteristic period. Variability due to gravitational or rotational effects is also taken into account. Recently, the variability classification of stars exhibiting stochastic frequency modes has been considered. The absolute magnitude values, given by the GAIA database, supports in making the color-magnitude H-R diagram for the analyzed targets. This should provide a reference to the main sequence and positions of the stars under study.
Keywords: Fotometria; Espectroscopia; Variabilidade estelar; Parâmetros evolutivos; Mag- nitudes absolutas do GAIA; Photometry; Spectroscopy; Stellar variability; Evolutionary parameters; Absolute magnitudes of GAIA; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA